Reframing Women’s Educational Leadership in Aceh: Rereading Fatmawati Soekarno through Sociohistorical Perspectives - Fonti Fai Banjarnahor; Rosmawaty Harahap (Journal of Aceh Studies, 2026)
A Women’s leadership in social development and education has been widely discussed in Indonesian scholarship, yet many studies continue to privilege national narratives while giving limited attention to regional socio historical contexts such as Aceh. Aceh possesses a distinctive tradition of women’s authority grounded in Islamic values, moral responsibility, and community-oriented education, which has rarely been examined in relation to national female figures. This study addresses this gap by critically reinterpreting the social and educational leadership of Fatmawati Soekarno through an Aceh centered analytical lens. The objective of this study is to examine how Fatmawati’s leadership ethos in education and social welfare resonates with Acehnese traditions of women’s leadership and to assess its relevance for Aceh Studies. Employing a qualitative interpretive research design, the study draws on historical and discursive analysis of primary documents and secondary scholarly literature related to Fatmawati, women’s leadership, education, and Acehnese socio cultural history. The findings reveal that Fatmawati’s leadership was predominantly articulated through moral authority, educational advocacy, and community oriented social care rather than formal political power. These characteristics closely align with established models of women’s leadership in Aceh, where legitimacy is grounded in ethical credibility, service, and educational engagement. An important finding is the strong discursive compatibility between Fatmawati’s national leadership ideals and Acehnese gender traditions, challenging assumptions that national female figures lack regional relevance. The study contributes to Aceh Studies by demonstrating the value of integrating national historiography with regionally grounded analysis. It offers theoretical and practical insights for understanding women’s leadership in education and social development within Aceh and comparable contexts.